ELM divertor peak energy fluence scaling to ITER with data from JET, MAST and ASDEX upgrade. (August 2017) - Eich, T.; Sieglin, B.; Thornton, A.J.; Faitsch, M.; Kirk, A.; Herrmann, A.; Suttrop, W.
Abstract: A newly established scaling of the ELM energy fluence using dedicated data sets from JET operation with CFC & ILW plasma facing components (PFCs), ASDEX Upgrade (AUG) operation with both CFC and full-W PFCs and MAST with CFC walls has been generated. The scaling reveals an approximately linear dependence of the peak ELM energy with the pedestal top electron pressure and with the minor radius; a square root dependence is seen on the relative ELM loss energy. The result of this scaling gives a range in parallel peak ELM energy fluence of 10–30 MJm −2 for ITER Q= 10 operation and 2.5–7.5 MJm −2 for intermediate ITER operation at 7.5 MA and 2.65 T. These latter numbers are calculated using a numerical regression ( ɛ I I = 0.28 M J m 2 n e 0.75 T e 1 Δ E E L M 0.5 R g e o 1 ). A simple model for ELM induced thermal load is introduced, resulting in an expression for the ELM energy fluence of ɛ II ≅6 π pe Rgeo qedge . The relative ELM loss energy in the data is between 2–10% and the ELM energy fluence varies within a range of 10 0.5 ∼ 3 consistently for each individual device. The so far analysed power load database for ELM mitigation experiments from JET-EFCC and Kicks, MAST-RMP and AUG-RMP operation are found to be consistent with both the scaling and the introduced model, ie not showing a further reduction with respect to their pedestal pressure. The extrapolated ELM energy fluencies are compared to material limits in ITER and found to be of concern.